Examining female entrepreneurial firms: can we predict growth orientation?. (17th December 2019) - Fleck, Emma
Both regional and global evidence presents a positive picture of increased entrepreneurial activity among females, and highlights, in particular, the rise in the rate of early stage entrepreneurs across both developed and emerging nations. However, it appears that a significant percentage of female-owned organisations remain small in size, with limited growth. Traditional growth models seem unable to account for this phenomenon and do not consider differences in gender as a causal factor. Consequently, this paper examines the growth orientation of female-owned firms in Ireland. Specifically, it identifies the factors that impact this process and provides clarity on predicting the growth trajectories based upon these entrepreneurial and organisational factors. As such, it aims to provide a mechanism to predict and stimulate high growth businesses among female entrepreneurs both within Ireland and across similar countries.